I’d rather be a cyborg than a gamerbro: How masculinity mediates research on digital play - Taylor, Nick (MedieKultur: Journal of media and communication research, 2018)
This article offers a feminist and media-theoretical approach to ethnographic reflexivity, understood as the researcher’s own agency in shaping encounters with and producing accounts of digital cultures. Looking specifically at male-dominated domains of intensive and competitive play in public sites, such as arcades, local area network (LAN) parties, and eSports tournaments, this article asks: How might masculinity mediate studies of digital play? To address this, I weave together feminist ethnography with materialist media theory, offering an understanding of researcher subjectivity (in this case, my subjectivity) as a media instrument: An assemblage of social locations and learned competencies which does not simply gather, but configures and legitimates, particular knowledges about gaming cultures. Applying this to a problematic instance from fieldwork I conducted at a large-scale gaming event in 2011, I work through the methodological and epistemological quandaries associated with both studying and embodying the social privileges associated with male-dominated media cultures.